Reason and less - Goel, Vinod (Frontiers in Psychology, 2014)
We consider ourselves to be rational beings. We feel that our choices, decisions, and actions are selected from a flexible array of possibilities, based upon reasons. When we vote for a political candidate, it is because they share our views on certain critical issues. When we hire an individual for a job, it is be-cause they are the best qualified. However, if this is true, why does an analysis of the direction of shift in the timbre of the voice of political candidates during an exchange or debate, predict the winner of American presidential elections? Why is it that while only 3% of the American population consists of white men over 6'4" tall, 30% of the CEOs of Fortune 500 companies are white men over 6'4" tall? These are examples of “instinctual biases” affecting or modulating rational thought processes. I argue that existing theories of reasoning cannot substantively accommodate these ubiquitous, real-world phe-nomena. Failure to recognize and incorporate these types of phenomena into the study of human reasoning results in a distorted understanding of rationality. The goal of the article is to draw attention to these types of phenomena and propose an “adulterated rationality” account of reasoning to explain them.